Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3390/foods9050590
|View full text |Cite
|
Sign up to set email alerts
|

Active Cardboard Box with Smart Internal Lining Based on Encapsulated Essential Oils for Enhancing the Shelf Life of Fresh Mandarins

Abstract: Mandarins are usually sold in bulk and refrigerated in open cardboard boxes with a relatively short shelf-life (12–15 days) due to physiological and pathological disorders (rot, dehydration, internal breakdown, etc.). The influence of a controlled release of essential oils (EOs) from an active packaging (including β-cyclodextrin-EOs inclusion complex) was studied on the mandarin quality stability, comparing different sized cardboard trays and boxes, either non-active or active, at the pilot plant scale (experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 44 publications
2
20
0
Order By: Relevance
“…Montero-Prado et al [ 57 ] also found that cinnamon EOs (non-encapsulated) included in active plastic containers seemed to reduce weight loss rates in peaches during cold storage. Similar weight loss inhibition with EOs (carvacrol, eugenol, thymol, menthol, eucalyptol, oregano EO, and cinnamon EO) has been found for other horticultural products [ 17 , 18 , 19 , 44 , 62 ]. Although the mechanism of this protective effect of EOs against weight losses in horticultural products is still not well known, Montero-Prado et al [ 57 ] found that lipoxygenase activity was inhibited in peaches stored within active EO (non-encapsulated) plastic containers.…”
Section: Resultssupporting
confidence: 70%
See 2 more Smart Citations
“…Montero-Prado et al [ 57 ] also found that cinnamon EOs (non-encapsulated) included in active plastic containers seemed to reduce weight loss rates in peaches during cold storage. Similar weight loss inhibition with EOs (carvacrol, eugenol, thymol, menthol, eucalyptol, oregano EO, and cinnamon EO) has been found for other horticultural products [ 17 , 18 , 19 , 44 , 62 ]. Although the mechanism of this protective effect of EOs against weight losses in horticultural products is still not well known, Montero-Prado et al [ 57 ] found that lipoxygenase activity was inhibited in peaches stored within active EO (non-encapsulated) plastic containers.…”
Section: Resultssupporting
confidence: 70%
“…Then, the four fruit samples were stored at 2 or 8 °C, leaving the jar lid half-closed to avoid fruit dehydration and O 2 reduction–CO 2 accumulation (O 2 ≥ 18% and CO 2 < 1%; measured with a portable CO 2 /O 2 analyzer (Checkpoint; PBI Dansensor, Ringsted, Danemark)) for 5 and 26 days. The cold storage period of 5 days was selected to simulate a short continental terrestrial transport, while the cold storage period of 26 days was selected to simulate long storage and overseas transport [ 17 , 24 ]. A commercialization simulation (COM; 4 days at 22 °C) was also conducted after each cold storage period to observe possible physiological disorders due to cold storage and real conditions during the commercial fruit retail period [ 1 , 2 , 24 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Weight of packages containing the product was monitored at each sampling time to determine the weight loss (%) of samples during storage ( 30 ). Dry matter content (%) was also monitored for lettuce as a good-quality index of solids changes (sugars and organic acids) during storage.…”
Section: Methodsmentioning
confidence: 99%
“…CDs have been used in food and pharmaceutical products for many years, largely to form inclusion complexes with problematic drugs to enhance their solubility [ 55 ]. In addition, previous studies have shown that CDs are useful as an antibacterial food packaging material when forming inclusion complexes with natural antimicrobial agents such as thymol and carvacrol [ 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 ]. This embedment of an antibacterial agent into food packaging material is one strategy to inhibit bacterial growth.…”
Section: Application Of Cyclodextrinsmentioning
confidence: 99%